Mayor Hubble is in trouble! - Gutman, Dan; Paillot, Jim (New York : Harper, an imprint of HarperCollins Publishers, 2012)
Mayor Hubble helps out and provides pointers when A.J. and Andrea square off in the school's presidential election.
The return of Mr. Wiggles -- The shut-up peace sign -- Rule the school -- Super secret strategy session -- Yuck! Kissing! Gross! -- On the stump -- How to wash a ferret -- The great debate -- Playing hardball -- Signs of trouble -- And the winner is... -- The runoff.
Ages 7-10.
Grades 2-5.
580L
Decoding demand: 83 (very high) Semantic demand: 95 (very high) Syntactic demand: 84 (very high) Structure demand: 82 (very high)
Accelerated Reader
Accelerated Reader AR
Keywords: A. J. -- (Fictitious character) -- Juvenile fiction; Ella Mentry School (Imaginary organization) -- Juvenile fiction; Elementary schools -- Juvenile fiction; Mayors -- Juvenile fiction; Schools -- Juvenile fiction; Student government -- Elections -- Juvenile fiction; Humorous stories